The Effectiveness of Push-Up Exercises on Increasing Accuracy Chest Pass in Basketball Games - Sariul; Marsuna (Athena: Physical Education and Sports Journal, 2026)
This study aims to determine the effectiveness of push-up training on improving chest pass accuracy in basketball games. This study used an experimental method with a one-group pretest-posttest design. The study population consisted of 236 students consisting of 105 male students and 131 female students. The sample was determined using a purposive random sampling technique based on the criteria of male gender, aged 16-18 years, having a height of 160–165 cm, and being able to perform a chest pass. From 65 students who met the criteria, a sample of 30 students was obtained through a randomization process. The research instrument used a basketball chest pass accuracy test. Data were analyzed using descriptive statistics to determine the average pretest and posttest scores, while hypothesis testing was carried out using a t-test at a significance level of 0.05. The results of the analysis showed that the t-value was 11.84, greater than the t-table of 2.042, so there was a significant difference between the pretest and posttest results after being given push-up training. These findings indicate that push-up training is effective in improving chest pass accuracy in basketball games.